Cancel culture can be collectively validating for groups experiencing harm - Marissa Traversa; Ying Tian; Stephen C. Wright (Frontiers in Psychology, 2023)
IntroductionSocial psychological research on collective action and intergroup harm has yet to adequately consider the potential role of cancel culture or feelings of collective validation in motivating collective action. The current research will begin to fill this gap and may broaden our understanding of the psychological mechanisms that inspire and maintain collective action in response to intergroup harm. To our knowledge, this research is the first social psychological analysis of the impact of cancel culture on collective action and as means for producing feelings of collective validation.MethodsIn two experimental studies, participants read a story describing an event of discrimination against their group followed by a manipulation of the presence or absence of an episode of cancel culture. Study 1 samples woman university students (N = 520) and focuses on their responses to a sexist incident on campus. Study 2 (pre-registered) assesses the generality of the model in a racism context with a community sample of East Asian Canadians and Americans (N = 237).ResultsStudy 1 showed that an episode of cancel culture had an indirect positive effect on collective action intentions mediated by feelings of collective validation and collective empowerment. Study 2 showed the indirect effect of cancel culture on collective action intentions mediated by feelings of collective validation and collective anger and contempt.DiscussionThe current research offers a novel theoretical and empirical introduction to the concept of collective validation and the understudied context of cancel culture to the existing social psychological research and theory on collective action. Further, cancel culture has been criticized as problematic. However, this perspective centres those in positions of power. Through this research, we hope to shift the focus onto marginalized groups’ perspectives of episodes of cancel culture. This research shows that groups who experience harm find these episodes of cancel culture validating in ways that have yet to be fully explored by intergroup relations research. Further, these findings suggest that collective validation does mediate the relationship between cancel culture and collective action; thus, cancel culture becomes an important contributor to resistance by marginalized groups through collective validation.